Przygotowanie procesu jako warunek efektywnego postępowania cywilnego - Gapska, Edyta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
It is considered as a widely shared view that Roman jurists were practically oriented, and so were Roman legal institutions, which evolved not on a baisis of theoretical explenations, but rather originated from a necessity of creating a good working, effective mechanism serving real needs of developing and constantly changing Roman society. Amongst Roman procedural regulations wchich were practically tested as useful and benefitial there are many of preparatory orientation, especially as far as in iure stage of a formulary proceedings is concerned. During this phase admissibility of a dispute was decided, as well as legal basis of a claim, an authority competent to decide upon a dispute and procedural plan fot the second stage. That orientation allows to consider whether in contemporary civil procedural rules proper attention is drawn to preparatory phase of civil litigation. The paper presents and specifies stances of parties prior to court hearing in choosen procedures in order to assess what measures are capable of ensuring greater effectiveness of civil proceeding through its proper preparation.